A survey of the mental health workforce in Guangdong: implications for policy and workforce planning. (December 2015) - Li, Yue; Jia, Fujun; Hou, Cailan; Ryan, Brigid; Blashki, Grant; Everall, Ian; Ng, Chee
Objective: Mental illness is a major contributor to disease burden in China. Guangdong province has a population of over 104 million. This province's health information system is inadequate, especially the mental health workforce and service response. This paper describes a field survey to assess the existing mental health workforce and service capacity in Guangdong. Method: A total of 125 major service providers in Guangdong were identified with the capacity to treat serious mental illness at all levels of the health system. These services were approached to complete a standardised survey based on the WHO Assessment Instrument for Mental Health Systems. Results: The survey identified 8498 mental health workers with 72.5% working in psychiatric hospitals. Service providers reported a treatment rate of 68.8% of a total of 430, 000 people registered for treatment of severe mental illness, and only 28.4% of over a million people estimated to be experiencing severe mental illness. An inadequate mental health workforce was cited as a common barrier to treatment access. Conclusion: Guangdong province has a significant treatment gap for severe mental illness and a shortage in the mental health workforce. The distribution of the mental health workforce and facilities is imbalanced towards hospital care rather than community care.